DGKZ Acts as a Potential Oncogene in Osteosarcoma Proliferation Through Its Possible Interaction With ERK1/2 and MYC Pathway - Yu, Wenxi; Tang, Lina; Lin, Feng; Yao, Yang; Shen, Zan (Frontiers in Oncology, 2019)
Osteosarcoma(OS) is the primary malignant bone tumor that most commonly affects children, adolescents, and young adults. However, survival rates continue to be unsatisfactory in the metastatic and relapse setting. Therefore, it is imperative to discover a novel target for more effective therapeutic interventions towards osteosarcoma. Diacylglycerol kinase zeta (DGKZ) is a recently identified gene potentially associated with certain human carcinogenesis. However, the expressional correlation and functional importance of DGKZ in osteosarcoma is still unclear. In this study, expression of DGKZ was firstly confirmed in OS sample tissues and correlated with poor prognosis in OS patients. Depletion of DGKZ by shRNA inhibited osteosarcoma cell proliferation and promoted cell apoptosis in vitro. In vivo, DGKZ silencing also suppressed xenograft tumor formation as determined by bioluminescence imaging and weight/volume measurements. Meanwhile, Affymetrix GeneChip and Ingenuity Pathway Analysis (IPA) demonstrated that DGKZ knockdown resulted in a decreased activity of MYC pathway, and several target genes expression in MYC pathway were altered, including CCND1, CDKN2B,CDK6,PCNA and EGR1.Furthermore, immunoprecipitation coupled with mass spectrometry (IP-MS) analysis was used to identify proteins that interacted with DGKZ in OS cells and revealed ERK1/2, a key MYC-interactor, to associate with DGKZ. Together, our study shows that DGKZ acts an oncogene in osteosarcoma via its possible interaction with ERK1/2 and MYC pathway.